Association between serum calcium and in-hospital mortality in critical patients with multiple myeloma: a cohort study. Issue 1 (31st December 2022) - Mao, Yafei; Zhu, Shumin; Geng, Yulan
ABSTRACT : Background: Elevated serum calcium levels may serve as a useful clinical biomarker of mortality in patients with multiple myeloma(MM). However, the clinical significance of the relationship between serum calcium levels and in-hospital mortality in MM patients admitted to the Intensive Care Unit (ICU) remains unclear. Objectives: This study aimed to explore the association between serum calcium levels and in-hospital mortality in patients with MM in the ICU. Methods: Patients with MM were identified from the Medical Information Mart for Intensive Care IV(MIMIC-IV) database. The outcome was in-hospital mortality. Multivariable-adjusted Cox regression analysis, curve fitting, and threshold effects analysis were used to assess the relationship between serum calcium levels and in-hospital mortality in patients with MM in the ICU. Results: Our study included 262 patients with MM with a mean age of 72.3 ± 11.0 years, 63.4% of whom were male. The in-hospital mortality was 19.5% (51/262). The relationship between serum calcium levels and in-hospital mortality was nonlinear. The effect size on the left and right sides of the inflection point, were 0.270 (HR: 0.270, 95% CI 0.106-0.687, P <  0.05) and 2.104 (HR: 2.104, 95% CI 1.069-4.142, P  < 0.05), respectively. The results of the sensitivity analysis remained stable. Conclusion: Our findings show that a nonlinear relationship exists between serum calcium levels and in-hospital mortality in critically ill patients with MM. A serum calcium level of approximately 8.40 mg/dL was associated with the lowest risk of in-hospital mortality, which increases with rising serum calcium levels, and should be of concern to ICU physicians.